Power Management Circuits for Low-Power RF Energy Harvesters - Michele Caselli; Marco Ronchi; Andrea Boni (Journal of Low Power Electronics and Applications, 2020)
The paper describes the design and implementation of power management circuits for RF energy harvesters suitable for integration in wireless sensor nodes. In particular, we report the power management circuits used to provide the voltage supply of an integrated temperature sensor with analog-to-digital converter. A DC-DC boost converter is used to transfer efficiently the energy harvested from a generic radio-frequency rectifier into a charge reservoir, whereas a linear regulator scales the voltage supply to a suitable value for a sensing and conversion circuit. Implemented in a 65 nm CMOS technology, the power management system achieves a measured overall efficiency of 20%, with an available power of 4.5 <semantics>μ</semantics>W at the DC-DC converter input. The system can sustain a temperature measurement rate of one sample/s with an RF input power of −28 dBm, making it compatible with the power levels available in generic outdoor environments.